Isolation of pure cassava linamarin as an anti cancer agent - Idibie, Christopher Avwoghokoghene (My University, 2008)
ABSTRACT Cassava is a known source of linamarin, but difficulties associated with its isolation have prevented it from being exploited as a source. A batch adsorption process using activated carbon at the appropriate contact time proved successful in its isolation with ultrafiltration playing a pivotal role in the purification process. Result revealed that optimum purification was obtained with increasing amount of crude cassava extract (CCE) purified. 60g of CCE took 32 mins, 80 g, 34 mins while 100 g took 36 mins of contact time, where 1.7 g, 2.0 g and 2.5 g of purified product were obtained, respectively. The purification process in batch mode was also carried out at different temperatures ranging from 25 to 65oC. Results showed that purification increases with increase in temperature. In a bid to ascertain the moles of linamarin adsorbed per pore volume of activated carbon used, the composite isotherm was found to represent the measured adsorption data quite well. The adsorption of linamarin was used to study the goodness of fit criteria (R2) for the entire process. Results showed that R2 value was best with decreasing amount of CCE purified (R2=1 for 60 g) at the temperature of 45oC. Compound elucidation of purified product by Picrate paper test, IR and 1HNMR confirmed the structure of linamarin. Cytotoxic effects of linamarin on MCF-7, HT-29, and HL-60 cells were determined using the 3 - (4, 5 – dimethylthiazol-2-yl) – 2, 5 – diphenyltetrazolium bromide (MTT) assay. Cytotoxic effects were significantly increased in the presence of linamarase, which catalysed the hydrolysis of linamarin to hydrogen cyanide. A 10–fold decrease in the IC50 values obtained for linamarin or crude extract in the presence of linamarase was determined for HL-60 cells. This study thus describes a method for the isolation and purification of linamarin from cassava, as well as the potential of this compound as an anticancer agent.
Keywords: cassava; linamarin; linamarase; adsorption; cancer cell lines